Performing In/formality beyond the Dichotomy: An Introduction - Koster, Martijn; Smart, Alan (Anthropologica, 2019)
This introduction to the special issue “Moving Beyond the Formal/Informal Dichotomy: Implications for Governance” provides an overview of recent debates on informality and argues in favour of understanding in/formality as a performance. Although informality and formality are often presented as opposing or even mutually excluding domains of social practice, ethnographic studies show how they coexist and are intertwined. Our special issue, with studies from the Philippines, Spain, Brazil and Mexico, concentrates on this intertwining of formality and informality, especially in the field of governance. Building upon these contributions to this issue, and the existing literature, this introduction approaches in/formality as a performance and examines the implications of such a view for our understanding of governance.